Labor market institutions and the future of work: good jobs for all? - Eichhorst, Werner; Rinne, Ulf (Bonn, 2017)
"Work and employment around the globe change continuously, but there are potentially more rapid and fundamental transformations ahead as new technologies can have major impact on what jobs will exist in the future, how people will work and how the global division of labor will evolve. This contribution tries to assess the current outlook into the foreseeable future and highlights the importance of labor market institutions that can effectively influence the future of work. The paper in particular addresses the need to reform and update labor market regulation, social protection and active labor market policies as well as the education systems."